Massive growth of a fibrous gas hydrate from surface macropores of an activated carbon. (16th January 2023) - Venet, Saphir; Derluyn, Hannelore; Guerton, Fabrice; Moonen, Peter; Broseta, Daniel; Brown, Ross
Highlights: Millimetres long bundles of hydrate fibres grow from surface macropores of a porous substrate. Surface macropores confirmed by confocal reflectance and scanning electron microscopies. X-ray radiography shows fluid exchange in the peripheral layers of the substrate. X-ray computed microtomography reveals a belt of organised peripheral porosity and connection to surface macropores. These features explain the unprecedented observation of comb or whale-bone like bundles of hydrate fibres. Abstract: Venet et al ., reported unprecedented, bundled growth of ≈ 1-10 mm long, hollow gas hydrate fibres, diameter ≈ 1-10 μ m, on an activated carbon close to a guest-water interface, circumventing the hydrate growth bottleneck. Here, in situ video microscopy traces growth (2-3 μ m s - 1 at 0.5 ° C) to surface macropores of similar diameter, further exhibited by confocal and scanning electron microscopies. X-ray radiography shows fluid exchange to a depth of ≈ 50-100 μ m in a total porous fraction 40 % (gravimetric porometry). Computed X-ray microtomography reveals a belt of organised peripheral porosity of aligned ≈ 5 μ m pores. These structures explain the origin of the comb or whalebone-like appearance of the hydrate. Whereas hydrate promotion by porous media is usually assumed to proceed inside the materials, like tiny hydrate storage warehouses, we find that the substrate behaves more like a 'lean' or 'just in time' production line, with hydrate extruded as fast as it is produced near the surface.